Analysis Of The Implementation Of E-Office X In The Business Archives Of PT X Head Office - Nadira Aulia Putri; Marsofiyati; Suherdi (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
This study aims to investigate the implementation of E-Office X on Business Archives at PT X Head Office. Data for this research were obtained through several methods, namely observation, interviews, and documentation. The data sources were selected using purposive sampling techniques. The analysis in this research was conducted using a descriptive analysis method to provide a comprehensive overview of how employees utilize the web-based E-Office in the systematic, factual, and accurate application of business archives based on the investigated facts. Therefore, this study is expected to provide in-depth insights into the utilization of E-Office on business archives and its impact on the administrative performance of PT X Head Office.